Eosin Y-catalyzed one-pot synthesis of spiro[4H-pyran-oxindole] under visible light irradiation. Issue 14 (3rd April 2020) - Chen, Meng-Nan; Di, Jia-Qi; Li, Jiao-Mian; Mo, Li-Ping; Zhang, Zhan-Hui
Abstract: An efficient and simple synthetic approach has been developed for the preparation of biologically interesting spiro[oxindole-3, 4'-(4′ H -pyran)] derivatives via visible light-mediated one-pot, three-component reaction of isatins, 1, 3-dicarbonyl compounds and malononitrile by using an inexpensive organic dye, Na2 eosin Y, as the photocatalyst in aqueous ethyl lactate at ambient temperature. The substrate scope of this three-component reaction is expanded to linear 1, 3-dicarbonyl compounds as viable starting materials. All rights reserved. Graphical abstract: Image 1 Highlights: A pot, atom and step economy, three-component reaction has been developed. The use of an inexpensive organic dye, Na2 eosin Y, as the photocatalyst, avoiding of any metal or acid catalysts. High yields and pure product formation at ambient temperature. The use of light as a rich, readily available and almost inexhaustible source of clean energy. Wide range of substrates, good product diversity and easy scalability.